Lung myofibroblast transition and fibrosis is regulated by circ0044226. (January 2020) - Zhang, Lijuan; Chi, Xiaowen; Luo, Wen; Yu, Shihuan; Zhang, Jiawen; Guo, Yuening; Ren, Qiu; Zhang, Wei
Abstract: Background and purpose: Idiopathic pulmonary fibrosis (IPF) is a life-threatening progressive disease characterized by aberrant fibroblast activation. This study aims to explore the role of the circ0044226 on fibroblast-to-myofibroblast transition (FMT). Methods: Bleomycin and TGF-β1 were respectively used to induce the IPF mice model and human lung fibroblasts to myofibroblast differentiation. The mRNA and protein levels were examined by qRT-PCR and western blot. Localization of α-SMA was evaluated by immunofluorescence staining. Cell viability and proliferation were evaluated by CCK8 and EDU test. Dual-luciferase reporter assay was used to analyze the interaction between miR-7 and circ0044226 or sp1. Fluorescence in situ hybridization (FISH) assay was used for the identification of sub-location of circ0044226 and miR-7 in cells. The IPF model mice received intratracheal injection of AAV-sh-NC and AAV-sh- circ0044226, and lung fibrosis was detected by HE staining, Masson staining and immunohistochemistry assay. Results: The circ0044226 was upregulated while miR-7 was downregulated in IPF mice model and FMT-derived myofibroblasts. miR-7 was a target of circ0044226 and sp1 was a target of miR-7. circ0044226 was distributed mostly in the cytoplasm and functioned as a miR-7 sponge to positively regulate the expression of sp1. Intervention of circ0044226 could ameliorate FMT and suppress fibroblast viability and proliferation by functioning as an endogenous miR-7 sponge. Conclusion: Circ0044226 knockdown alleviates fibroblast proliferation and FMT by functioning as a competing endogenous RNA, which may represent a promising therapy for pulmonary fibrosis.